2016
DOI: 10.1002/pros.23195
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB and androgen receptor variant 7 induce expression of SRD5A isoforms and confer 5ARI resistance

Abstract: BACKGROUND Benign prostatic hyperplasia (BPH) is treated with 5α-reductase inhibitors (5ARI). These drugs inhibit the conversion of testosterone to dihydrotestosterone resulting in apoptosis and prostate shrinkage. Most patients initially respond to 5ARIs; however, failure is common especially in inflamed prostates, and often results in surgery. This communication examines a link between activation of NF-κB and increased expression of SRD5A2 as a potential mechanism by which patients fail 5ARI therapy. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 70 publications
3
31
0
Order By: Relevance
“…Noteworthy, in adenomas we have detected the highest SRD5A2 RE levels. It is known that increased SRD5A2 in adenomas provokes hyperplasia extension through NF-kB and AR isoform 7 conferring 5α-reductase inhibitors resistance [26]. From other hand decreased levels of SRD5A2 in adenocarcinomas is associated with the enhanced cell migration and invasion [7].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, in adenomas we have detected the highest SRD5A2 RE levels. It is known that increased SRD5A2 in adenomas provokes hyperplasia extension through NF-kB and AR isoform 7 conferring 5α-reductase inhibitors resistance [26]. From other hand decreased levels of SRD5A2 in adenocarcinomas is associated with the enhanced cell migration and invasion [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple mechanisms have been proposed to explain escape from ADT (such as AR amplification, modification of the AR by point mutations or phosphorylation, and changes in AR co-activators), recent studies have demonstrated that the elevated expression of ARVs is an important driving force in developing CRPC [ 1 5 ]. We have shown that activation of NF-κB signaling increases ARVs (AR-V7) in benign prostatic tissue [ 8 ], PC [ 9 ], and NF-κB/AR-V7 increases expression of steroid-5α-reductase type II, the enzyme which converts testosterone to dihydrotestosterone, the most active androgen [ 61 ]. In support of our reports, Nadiminty et al demonstrated that NF-κB regulates expression of ARVs in CRPC [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Castration induces cell death and inflammation in the prostate, which needs to be controlled by macrophages [ 42 ], but these immunosuppressive myeloid cells can also contribute to the development of castration-resistant prostate cancer [ 43 ]. Noteworthy, induction of endogenous androgen biosynthesis in prostate cancer cells is at least partially driven by NF-κB, and might thus also be promoted by inflammation induced by castration [ 44 ].…”
Section: Introductionmentioning
confidence: 99%